Pertanggungjawaban Hukum terhadap Pelaku Tindak Pidana Pemberian Keterangan Palsu secara Menyesatkan kepada Penerima Fidusia ditinjau dari Undang-Undang Nomor 42 Tahun 1999 (Studi Putusan Nomor 75/Pid.Sus/2024/PN.Tjk) - Leicha Yarra; Zainab Ompu Jainah (Lembaga Yasin AlSys, 2025)
This study is motivated by the legal accountability issues surrounding perpetrators of criminal acts involving the provision of misleading false statements to fiduciary recipients, which constitutes a violation of the principle of trust in fiduciary security agreements. Providing false information not only causes legal and economic harm to the fiduciary recipient but also undermines the validity of the collateral object itself. The objective of this research is to analyze the forms of legal accountability imposed on such offenders based on Law Number 42 of 1999 concerning Fiduciary Security, through a case study of Decision Number 75/Pid.Sus/2024/PN.Tjk in the Bandar Lampung jurisdiction. The research employs a normative juridical method, using statutory, legal theory, and judicial decision approaches. The findings indicate that perpetrators may be subject to criminal sanctions under Article 35 of Law Number 42 of 1999 and, in specific cases, may also be charged under provisions in the Indonesian Criminal Code (KUHP) relating to fraud or data falsification. Legal enforcement against such offenders is essential to create a deterrent effect and to ensure legal protection for fiduciary recipients. This study recommends stricter oversight of fiduciary agreement implementation and improved public legal literacy regarding the legal consequences of providing false information in fiduciary practices.